Gastrointestinal Manifestations in Patients with Chronic Kidney Disease (Academia Journal of Medicine, 2019)
Background: Chronic kidney disease is a silent epidemic of the 21 century. Surveys have suggestedthat as many as 16% of the adult  population have CKD1. The most common, non –renal, chronic disorders in patients with ESRD are gastro intestinal disorders2. Among upper gastrointestinal lesions caused by chronic kidney disease gastritis, an esophagus is,gastric ulcers are the most prevalent lesions. Here an attempt  is being made to study the upper gastro intestinal changes in chronic kidney disease and evaluate theirrelationship with the stage of CKD or  GFR. Objectives: 1. To determine the prevalence of various upper gastro intestinal lesions withthe use of fibro optic endoscopy.2. To evaluate  the relation between the gastro intestinal lesion with the stage ofCKD or GFR. Subjects and Methods: We conducted a cross sectional study  on 50 patients ,who are diagnosed to haveChronic kidney disease and being presented to OPD and admission in NavodayaMedical College and  Research Center, Raichur over a period of one year. All patientswith chronic kidney disease underwent upper gastrointestinal endoscopy  wereincluded in the study. Results: Majority of the subjects belongs to age group of 31 to 40 years (26%) and least belongs to 70 to 80 years  age group (6%).Out of the 50 subjects, males were 28 and females were 22.Majority of the cases in our study belonged to stage IV. 84% of the  cases had upper gastrointestinal involvement on endoscopic examination in our study. Erosive gastritis (26%), either antral or fundal, was the  predominant lesion found on endoscopy. Majority of the subjects having erosive gastritis, had stage IV CKD (53.8%).Out of 50 cases in our study 55% of subjects had lesions of the stomach, 26% of subjects had lesions in the duodenum, 19% of subjects had lesions in esophagus. Out  of 50 subjects in our study 52% were undergoing haemodialysis and 48% of subjects were under conservative management. Majority of  subjects undergoing haemodialysiswere belongs to stage V. Conclusion: Majority of the patients with chronic kidney disease have upper  gastrointestinal involvement on endoscopic evaluation. Erosive gastritis is the most common upper gastrointestinal manifestation in our study.  Upper gastrointestinal manifestations are predominant in stage V. Upper gastrointestinal findings are frequently observed in chronic kidney  disease patients on dialysis. Early diagnosis and management can reduce mortality and morbidity and prevent fatal complication like massive  upper gastrointestinal bleed.
Keywords: Chronic kidney disease; Upper gastrointestinal manifestations; Erosive gastritis